EFFECTIVENESS EFFECTIVENESS OF IMPLEMENTATION POSTPARTUM CARE MODULE ON THE WOUND HEALING OF PERINEUM LACERATION - Gita Nirmala Sari; Diana Hartaty Angraini; Erika Yulita Ichwan; Nurjasmi Nurjasmi (Jurnal Ilmiah Bidan (JIB), 2020)
There are three important factors that effect of the wound healing of perineum laceration, namely mobilization, nutrition and cleanliness of vulva and perineum. With the fulfillment of the three factors become 1 package of module, it can be happening faster of wound healing in the proliferation phase of perineum laceration less than 7 days, which is usually occur more than 7 days. The purpose of this research was to know the effectiveness of the implementation of the package of modules in accelerating wound healing the perineum at the proliferation phase. The population of this study were post partum mothers with 2nd grade of perineum laceration in the place of research that chosen by simple randomization and randomized allocation that matching with inclusion and exclusion criteria. 18 mothers were selected as intervention group, while 18 mothers were selected as control group in different health center. This research used true quantitative experimental design with posttest only control group design and use chi-square test analysis for categorical variables throughout and logistic regression for multivariable analysis. There was a significant association between implementation module with long time of wound healing of perineum laceration in the proliferation phase (p value = 0,002) with OR (95%CI) was 60 (3.14 – 1147.29) before compared with control group. Mothers who implemented of module have probability for faster of wound perineum healing < 7 days postpartum compared with control group with OR (95% CI) was 5.5 (1.27 – 23.69). Implementation of the module package was very effective in accelerating the healing of wounds in the proliferation of the perineum laceration.